Phytochemical analysis of Gloriosa superba L. Using GC-MS from five different ecotypes of Tamil Nadu State, India - Paul Jasmine, J.A.; Sundari, T.; Balakrishnan, V. (Current Botany, 2020)
Gloriosa superba L is an important medicinal plant and its seeds, tubers are used for medicine. To investigate the phyto-components of Gloriosa superba L collected from various habitats of Tamil Nadu state, India. In the present study, the phyto-components from the tubers of Gloriosa superba L cultivars from Sirumalai (GA1) Mulanoor (GA2), Thuraiyur (GA3), Konganapuram (GA4) and Vedaranyan (GA5) were extracted by ethanolic extract and the composition of chemicals and its concentration in the tubers were determined by Gas Chromatography – Mass spectrometry (GC-MS) analysis.Among the phyto-components GA1 shows 15 phyto-components, GA2 shows 13 phyto-components, GA3 shows that 8 phyto-components, GA4 shows 14 phyto-components and GA5 shows 13 phyto-components. GA1, GA2, GA4 and GA5 ecotypes possessed higher phyto-components. Colchichine is an important alkaloid of Gloriosa superba L was found in GA2, GA3, GA4 and GA5 accessions in good concentration. The results reveals that the geographical origin and climate condition of a accession causes polymorphisms in the accumulation of phyto-components, its composition and morphological traits in Gloriosa Superba L originating from different ecotypes of Tamil Nadu state.